Scan QR code or get instant email to install app

Skip to content
#
Use the distributive property to expand the given expression:

\(-8(4u^2-6v^2)\) =

### Related Information

Question:

\(-8(4u^2-6v^2)\) =

`_________`

.
A
\(-32u^2+48v^2\)

explanation

Use the distributive property to expand the expression, and then use order of operations to simplify. Apply the distributive property.

\(-8(4u^2-6v^2)\)

\(= -8(4u^2)-(-8)(6v^2)\)

\(= -32u^2+48v^2\)

Take more free practice tests for other GED topics with our ged practice test now!

Comments